Discourse Analysis of Consumer Behavior in the Film Crazy Rich Asian (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study focuses on the consumerism depicted in the Crazy Rich Asian flicks. The theories used in this study include communication theory, cinema theory, consumptive behaviour, consumptive lifestyle, and discourse analysis. This study employs descriptive qualitative research methodologies, including discourse analysis combined with a case study methodology. The subjects in this study are Crazy Rich Asian flicks, while the objective are consumption habits. Data collecting techniques include observation and the study of literature. The Teun A. Van Dijk model discourse analysis was used to analyse the data. The results of this study reveal that the built consumptive lifestyle is the way a person demonstrates his identity via the use of time, money, and luxury products that lead to.